2016
DOI: 10.17705/1cais.03912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Information Technology (IT) Security Information Sharing among Competing IT Firms on Firm’s Financial Performance: An Empirical Investigation

Abstract: Traditionally, IT firms closely guard the management and control of critical information assets. A group of IT firms, however, adopted a different approach and formed an organization with the goal of sharing critical IT security information with industry peers (firms in the same industry that do not directly compete) and competitors to more effectively manage IT security. The inherent vulnerability in sharing critical information with other (potentially competing) firms presents an interesting, coopetition par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
(136 reference statements)
0
6
0
Order By: Relevance
“…In the study [48] it was proven for publicly listed cyber-security and IT firms that participate in sharing IT security-related information have higher profitability and lower costs than non-participating IT firms (in short and in a long-run term). Later, the same team of researchers argued that there are few studies on how IT security strategy impacts firm performance and more investigations, in particular, theory-based empirical research, are needed, especially when the companies continue to engage in "various forms of cooperation, alliances and coopetition" [49].…”
Section: Advanced Search and Content Analysismentioning
confidence: 98%
“…In the study [48] it was proven for publicly listed cyber-security and IT firms that participate in sharing IT security-related information have higher profitability and lower costs than non-participating IT firms (in short and in a long-run term). Later, the same team of researchers argued that there are few studies on how IT security strategy impacts firm performance and more investigations, in particular, theory-based empirical research, are needed, especially when the companies continue to engage in "various forms of cooperation, alliances and coopetition" [49].…”
Section: Advanced Search and Content Analysismentioning
confidence: 98%
“…Moreover, the quality indicators obtained with the metrics were compared to the perceptions of quality provided by ontology engineers. The Energies 2022, 15, 2170 3 of 23 study demonstrated that quality was an essential factor for the acceptance of technologies and solutions and the usability of products. Ling et al [4] researched the use of information technologies among school educators in Malaysia.…”
Section: Applicabilitymentioning
confidence: 99%
“…Based on a game-theoretic model, the authors devised improvements to the membership policies to evade the problem of passive, advantage-taking participation and a lack of information sharing. Additionally, Appan et al [14] investigated the motivations for joining an ISAC. Their analyses focused on the Information Technology Information Sharing and Analysis Center (IT-ISAC) established by a group of IT enterprises.…”
Section: Information Sharing and Analysis Centresmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, although the financial services sector has managed to share some information, competition among firms has long retarded such efforts; it also prevents information-sharing whenever firms are faced with potential losses after a breach (interviews with Tico 2019 and Brooklyn 2019). The situation is most problematic in telecommunications and information technology, where firms not only see one another as commercial competitors (Appan and Bačić 2016) but also perceive cybersecurity itself to be a source of competitive advantage and actively market the security of their systems to customers (interview with Wilhelm 2019).…”
Section: Explaining Success Across Sectorsmentioning
confidence: 99%